The impact of fiscal loss compensation and corporate governance on tax avoidance: The moderating role of foreign share ownership - Muhammad Daniel NA; Yuliansyah Yuliansyah; Reni Oktavia (Global Academy of Multidisciplinary Studies, 2025)
Purpose: This study examines the influence of fiscal loss compensation and corporate governance, proxied by independent commissioners and the audit committee, on tax avoidance, with foreign ownership as a moderating variable in Indonesian manufacturing companie. Research/methodology: A quantitative design was applied using purposive sampling of 65 manufacturing companies listed on the Indonesia Stock Exchange during 2020–2024, producing 280 valid observations. Data were collected from financial statements accessed via the IDX and company websites. The analysis employed descriptive statistics, classical assumption tests, multiple regression, and moderated regression analysis (MRA). Results: The findings reveal that fiscal loss compensation significantly increases tax avoidance, while independent commissioners and the audit committee reduce it. Foreign ownership does not directly affect tax avoidance but moderates the relationships. Specifically, foreign ownership weakens the negative effects of independent commissioners and the audit committee on tax avoidance, whereas it does not moderate the relationship between fiscal loss compensation and tax avoidance. Conclusions: Corporate governance mechanisms remain crucial in mitigating tax avoidance, but the presence of foreign shareholders creates complex dynamics that may undermine governance effectiveness. Limitations: The study focuses only on manufacturing firms within a five-year period and relies on secondary data, limiting generalization across industries and contexts. Contribution: This research contributes to the literature by integrating fiscal loss compensation, corporate governance, and foreign ownership into tax avoidance studies in emerging markets. Practically, the findings offer guidance for policymakers and investors to enhance governance mechanisms and reduce tax avoidance risks.